Dapatkah Penghasilan Komprehensif Lainnya Digunakan sebagai Media Tindakan Kecurangan Laporan Keuangan? - Kusumaningarti, Miladiah; Kusuma, Marhaendra; Athori, Agus (Jurnal Akuntansi dan Governance, 2025)
Objectives: This study aims to prove that Others Comprehensive Income (OCI) fair value hierarchy and presentation of plans realize fraudulent financial statement.Design/method/approach: The data observed are 1,890 companies listed on the IDX for all industrial sectors for the period 2021-2023. Hypothesis were tested with multiple linear regression analysis.Results/findings: We found that OCI level 3 has a significant positive effect on the fraudulent financial reporting proxied by Beneish M Score. While OCI Reclassification has a significant negative effect on the Beneish M Score.Theoretical contribution: The low quality of fair value input or the high subjectivity of management can be a medium for financial reporting fraud, but accounting standard regulations regarding the submission of unrealized earnings plans for the current period have been proven to be able to reduce the potential for fraud.Practical contribution: The actuarial profession in determining the fair value of level 3 input must be based on professional considerations, not on management orders.Limitations: OCI is only classified based on the fair value hierarchy and reclassification, even though it can also be based on the presence or absence of final tax burdens, which are relevant to fraud through tax avoidance